(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
This article examines the architectural and historical development of the Dorus Saodat memorial and religious complex in Shahrisabz, Uzbekistan. Emphasis is placed on the unique design and construction of the crypt originally intended for Amir Temur, which is considered one of the most magnificent funerary structures in Central Asia and the Islamic world. Drawing upon historical texts, scholarly sources, and archaeological investigations – particularly the fieldwork conducted by Kh.T. Sultanov – the study presents a graphic reconstruction of the complex as a remarkable example of Timurid Renaissance architecture.